A (in)aplicabilidade do “princípio” do in dubio pro societate na decisão de pronúncia do Tribunal do Júri: análise da interpretação do Supremo Tribunal Federal - Carvalho, Leonardo Silva (2020)
This research aims to analyze the application of the in dubio pro societate principle in court order decisions entered judgement in the jury trial procedure, especially about the interpretation of the Federal Supreme Court regarding this principle. The theme choice is justified by the lack of studies that persue how courts have perceived said principle, since many of the scientific studies about this subject prefer juristic, theoretical discussions. The research starts from the question: How has the Supreme Federal Court interpreted the enforcement of the in dubio pro societate principle in the jury trial’s court order decision? One hypothesis is that the Federal Supreme Court takes part as in the informative 935’s direction, and thus, not accepting the principle of in dubio pro societate application in court order decisions. This essay’s goal is to understand the Supreme Federal Court’s interpretation, based on appellate decisions entered judgement from 1996 to 2020, as well as to understand the nature and possible effects of the application of this legal axiom. To do so, it is necessary to present possible theoretical statements, regarding the application of such principle in the court order decision, moving, then, to a qualitative empirical approach, whose technique is the case law analysis. Therefore, it can be verified that the Federal Supreme Court is in favor of the in dubio pro societate enforcement in court order decisions, which imposes the acknowledgement that such an interpretation is antagonistic to the opinions of jurists and literature on the subject. This verification implies, consequently, in the investment of the in dubio pro reo principle, which causes an omission of the first phase of the jury trial, given the possibility for the judges to excuse themselves from their role, referring the doubt solution back to the popular jury under the allegation of predominance of society’s interest and verdicts’ sovereignty.